Critical success factors for high routine immunization performance: A case study of Nepal. (December 2022) - Hester, Kyra A.; Sakas, Zoe; Ellis, Anna S.; Bose, Anindya S.; Darwar, Roopa; Gautam, Jhalak; Jaishwal, Chandni; James, Hanleigh; Keskinocak, Pinar; Nazzal, Dima; Awino Ogutu, Emily; Rodriguez, Katie; et al.
Highlights: Nepal reported high and sustained immunization coverage compared to peers. National and multi-national partnerships supported information sharing, division of labor, and mutual capacity building. Pro-vaccine messaging through various mediums, including Female Community Health Volunteers, which was tailored to local needs, generated public awareness. Cultural values fostered collective responsibility and community ownership of vaccine coverage. Abstract: Introduction: The essential components of a vaccine delivery system are well-documented, but robust evidence on how and why the related processes and implementation strategies drive catalytic improvements in vaccination coverage are not well established. To address this gap, we identified critical success factors that may have led to substantial improvements in routine childhood immunization coverage in Nepal from 2000 through 2019. Methods: We identified Nepal as an exemplar in the delivery of early childhood immunization through analysis of DTP1 and DTP3 coverage data. Through interviews and focus group discussions at the national, regional, district, health post, and community level, we investigated factors that contributed to high and sustained vaccine coverage. We conducted a thematic analysis through application of implementation science frameworks to determine critical success factors. We triangulated these findings with quantitative analyses using publicly available data. Results: The following success factors emerged: 1) Codification of health as a human right, - along with other vaccine-specific legislation - ensured the stability of vaccination programming; 2) National and multi-national partnerships supported information sharing, division of labor, and mutual capacity building; 3) Pro-vaccine messaging through various mediums, which was tailored to local needs, generated public awareness; 4) Female Community Health Volunteers educated community members as trusted and compassionate neighbors; and 5) Cultural values fostered collective responsibility and community ownership of vaccine coverage. Conclusion: This case study of Nepal suggests that the success of its national immunization program relied on the engagement and understanding of the beneficiaries. The immunization program was supported by consistent and reliable commitment, collaboration, awareness, and collective responsibility between the government, community, and partners. These networks are strengthened through a collective dedication to vaccination programming and a universal belief in health as a human right.